Learning Design for Light Wave Oriented to the Multiple-Representations of High School Students in East Aceh - Yakob, Muhammad; Putri, Mentari Darma; Muhammad, Guntur Maulana (Indonesian Journal of Science and Mathematics Education, 2023)
Several studies have shown a deficiency in multiple-representation skills among high school students in East Aceh, where the learning process has not fully accommodated the development of these skills. This research aims to develop a learning design focused on enhancing students' multiple-representation abilities in the subject of light waves. The methods used include surveys and design research, with data collection utilizing validation sheets, pretests, posttests, and interviews. The validation results indicate a very valid category for question instruments, worksheets, and media. An initial survey of 30 high school students in East Aceh revealed an average initial multiple-representation ability of 28.4%. After limited implementation of the learning design, students' multiple-representation ability increased to an average of 61.8%. Thus, this learning design has proven effective in enhancing students' multiple-representation skills. Future research could evaluate its application in other subject materials.